Corporate social responsibility and brand management: evidence from Carroll’s pyramid and triple bottom line approaches - Štreimikienė, Dalia; Ahmed, Rizwan Raheem (Technological and Economic Development of Economy, 2021)
The objective of this research is to evacuate the relationship between CSR initiatives and organizational performance. Additionally, the undertaken research examines the impact of brand image and brand awareness as mediators and corporate image as the moderator between CSR initiatives and organizational performance. We employed a modified conceptual framework derived from the Triple bottom line and Carroll’s pyramid models. The data was analyzed through the structural equation model by using confirmatory and exploratory factor analyses and conditional process approach for examining the direct, mediating, and moderating hypothesized relationships. The undertaken study’s outcomes demonstrated that the ethical, philanthropic, and sustainable dimensions positively and significantly influence organizational performance. Similarly, the mediation analysis suggested that the brand image and brand awareness are the potent mediators in an association between ethical, philanthropic, and sustainable dimensions and organizational performance. Findings further demonstrated that corporate image as a moderator has strong impact between exogenous factors and organizational performance. The undertaken study has important theatrical and managerial implications that provide value additions for both researchers and industry practitioners.